Method for simultaneously optimizing squareness and residual magnetism temperature coefficient of 2 / 17 type samarium-cobalt sintered magnet
By using heavy rare earth elements to replace Sm elements in the 2:17 samarium-cobalt sintered magnet and performing isothermal annealing after the ingot annealing, the problem of insufficient stability and magnetic performance of the magnet at high temperatures is solved, and excellent residual magnetic temperature coefficient and coercive force are achieved.
Patent Information
- Application Number
- CN202411394557.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-03-14
AI Technical Summary
The existing 2:17 samarium-cobalt sintered magnets are difficult to meet the requirements of high stability and comprehensive magnetic properties at high temperatures, especially in terms of residual magnetic temperature coefficient and coercive force.
By replacing the Sm element in the Sm(CoFeCuZr)z alloy with heavy rare earth elements and performing isothermal annealing after the ingot annealing, the residual magnetic temperature coefficient and squareness of the magnet are regulated.
It realizes a low residual magnetic temperature coefficient in the range of 20-200℃, while improving the coercive force and high-temperature usage stability of the magnet, enhancing the overall magnetic performance.
Smart Images

Figure SMS_1 
Figure HDA0005073404950000011 
Figure HDA0005073404950000012
Abstract
Description
Technical field:
[0001] The invention provides a method for simultaneously optimizing the squareness and remanence temperature coefficient of a 2:17 type samarium-cobalt sintered magnet, and belongs to the technical field of rare earth magnetic material preparation. Background technology:
[0002] 2:17 type samarium cobalt sintered magnets have become an irreplaceable choice for high temperature applications due to their high Curie temperature, excellent temperature coefficient and excellent comprehensive magnetic properties. Conventional samarium cobalt permanent magnets cannot meet the current requirements of high stability and comprehensive magnetic properties. Existing commercial samarium cobalt permanent magnets require that the magnets maintain a residual magnetic temperature coefficient (α) between ±0.01% / °C in the range of 20-200°C. However, the permanent magnets with low residual magnetic temperature coefficients prepared in the literature only have a low temperature coefficient between 25 and 150°C and cannot be used at higher temperatures.
[0003] By using heavy rare earth elements (Dy, Er, Gd and Tm, etc.) to replace Sm (Co, Fe, Cu, Zr) z The Sm in the alloy can achieve the effect of compensating the remanent magnetization temperature coefficient, but it will inevitably lead to the reduction of the remanence and coercivity of the magnet. In order to improve the magnetic properties of magnets, especially the remanence and coercivity of magnets, researchers have conducted a lot of research work, mainly including multi-component heavy rare earth substitution, doping of new alloy components, and using rare earth spin reorientation to obtain excellent coercivity temperature coefficient. The first method: as in patent CN113436819A, different Gd and Dy are used to replace each other to obtain higher remanence and improve the remanence temperature coefficient, but the coercive force is low; the second method: as in patent 201310035673.6, rare earth self-selected reorientation is used to obtain the simultaneous stability of coercive force and remanence temperature coefficient, but the compensation range is narrow; the third method: as in patent CN201911347976.5, alloy ingots Sm (CoFeCuZr) z alloy and RE (Dy, Er, Ho, Tb, Lu) CuZr alloy are prepared separately, and the alloy powders are mixed to reduce the use of heavy rare earths and retain a higher remanence, but the remanence temperature coefficient (-0.02-0.03% / ℃) cannot meet the current commercial magnet requirements (-0.01-0.01% / ℃), and the process steps are increased, which increases the cost. The processes currently used to improve the temperature dependence of the remanence of 2:17 type samarium cobalt sintered magnets using the above methods all face different disadvantages.
[0004] Therefore, a new component design and preparation process is urgently needed to improve the compensation ability of heavy rare earths, so that while achieving excellent remanence temperature coefficient and high remanence, it can also maintain a high coercive force and improve the squareness (Q) of the demagnetization curve so that the magnet can obtain better magnetic properties. Squareness Q: The ratio of Hk to HcJ (Hk / HcJ) is used to represent the squareness Q of the demagnetization curve. The value range of Q is between 0 and 1. The closer Q is to 1, the closer the demagnetization curve is to a square. It is generally believed that products with squareness Q>0.9 are qualified products. Therefore, a low-cost, simple process, Sm with both low temperature coefficient and high comprehensive magnetic properties is obtained. 2 Co 17 Sintered magnets are of great significance. Summary of the invention:
[0005] In view of the above problems, the present invention provides a method for simultaneously optimizing the squareness and remanent temperature coefficient of 2:17 type samarium cobalt sintered magnets. By using heavy rare earth elements to replace the Sm element in the Sm (CoFeCuZr) z alloy, on the one hand, the remanent temperature coefficient of the magnet can be regulated by controlling different substitution amounts; on the other hand, the squareness can be improved by combining isothermal annealing of the ingot alloy. This is because the uniformity of element distribution in the alloy is improved after ingot annealing, the substitution sites of heavy rare earth are increased, the compensation effect of heavy rare earth is enhanced, and the absolute value of the remanent temperature coefficient is reduced. In addition, due to the uniform distribution of elements in the microstructure, the grain boundary defects are repaired, so that the H of the magnet is k It has been significantly improved, increasing the high-temperature stability of the magnet.
[0006] The specific preparation process includes: melting ingot-isothermal annealing-powder making-oriented pressing-sintering-solid solution-aging, etc. In particular, the present invention adds an isothermal annealing process after melting the ingot, which inhibits the generation of 2:17H in the ingot and improves element segregation, thereby improving the component uniformity in the alloy. Therefore, it is easier to obtain a more uniform supersaturated solid solution after solution treatment, thereby improving the cellular structure in the magnet after aging and improving the performance of the magnet.
[0007] A method for simultaneously improving the knee point and remanence temperature coefficient of a 2:17 type SmCo-based sintered magnet, characterized in that the alloy composition is Sm 1-x RE x (Co,Fe,Cu,Zr) z , where RE = one or more of heavy rare earth elements such as Dy, Er, Gd and Tm. Smelting is carried out under the protection of argon gas, and an ingot is obtained after being poured into a copper mold. The ingot obtained by smelting is isothermally annealed at 1190-1210°C for 5-20h, and then a magnet is obtained according to a conventional powder metallurgy process.
[0008] The nominal composition of the alloy is Sm 1-x REx (Co bal Fe a Cu b Zr c ) z , where RE is a heavy rare earth element. a, b, c, x satisfy the following relationship: 0≤x≤0.6, 0.1≤a≤0.2, 0.06≤b≤0.12, 0.02≤c≤0.03, 6.9≤z≤7.9, bal refers to 1-abc.
[0009] A method for simultaneously optimizing the squareness and remanence temperature coefficient of a 2:17 type samarium cobalt sintered magnet, the steps of which are as follows:
[0010] (1) Based on the nominal composition of the alloy: Sm 1-x RE x (Co bal Fe a Cu b Zr c ) z Select rare earth, metal cobalt, metal iron, metal copper, metal zirconium, put them into a crucible, fill them with argon gas for smelting after the materials are baked under vacuum, and then pour them into a water-cooled copper mold to obtain an ingot with a thickness of 1.8-2.0 cm;
[0011] (2) heating the ingot obtained in step (1) to 1190-1210° C. in a tube furnace, filling it with argon gas, performing isothermal annealing for 5-20 hours, and then air cooling;
[0012] (3) the ingot in step (2) is coarsely crushed in a medium crusher, 1.5-3 wt.% of an antioxidant is added to prevent oxidation, and then the ingot is ground into a powder with a particle size of about 3.5-4.5 μm by a jet mill process;
[0013] (4) Adding 1.5-3.0 wt.% of an antioxidant to the powder obtained in step (3) in a glove box to prevent oxidation and increase lubrication, and then mixing in a three-dimensional mixer for 2-5 hours;
[0014] (5) placing the powder obtained in step (4) in a magnetic field of 1.7-2.0 T for arrangement and pressing, and then pressing and molding by cold isostatic pressing at a pressure of 200-280 MPa and a holding time of 120-180 s;
[0015] (6) placing the green body obtained in step (5) into a vacuum sintering furnace for sintering and solution treatment, sintering the green body at 1210-1230° C. for 1-5 hours, then performing solution treatment at 1150-1200° C. for 5-30 hours, and finally air cooling to room temperature, thereby obtaining a supersaturated solid solution;
[0016] (7) The solid solution magnet obtained in step (6) is placed in a tubular furnace, and then the solid solution sample is isothermally aged at 810-850°C for 10-20 hours under the protection of argon, and then slowly cooled to 400°C at a rate of 0.5-0.8°C / min, and isothermally aged at 400°C for 3-6 hours to obtain a SmRE(CoFeCuZr)z magnet.
[0017] The sintering process and the solid solution process are further selected according to the heavy rare earth content. The larger the heavy rare earth element content (x), the longer the sintering time and the higher the solid solution temperature in step (6). Compared with the conventional 2:17 type samarium cobalt magnet, the longer sintering time can obtain a dense magnet with larger grain size and more uniform composition; the high solid solution temperature in step (6) further promotes element diffusion to obtain a supersaturated solid solution with uniform composition.
[0018] Compared with the prior art, the present invention has the following advantages:
[0019] (1) The present invention uses heavy rare earth elements to replace samarium, and controls the remanence temperature coefficient by controlling the type and content of the heavy rare earth elements.
[0020] (2) The present invention adds isothermal annealing of the ingot to the conventional 2:17 samarium cobalt magnet preparation process. The prepared magnet not only has a good remanence temperature coefficient, but also can significantly improve the squareness of the 2:17 SmCo-based magnet, thereby improving the comprehensive magnetic properties and enhancing the temperature compensation effect of the heavy rare earth elements.
[0021] (3) In the present invention, by adding an isothermal annealing process, on the one hand, the content of 2:17H phase in the ingot can be reduced, the crystal stress and defects generated during casting can be eliminated, and the ingot structure can be uniform after isothermal annealing, which can suppress large-scale element segregation and help suppress subsequent composition inhomogeneity problems; on the other hand, isothermal annealing is beneficial to subsequent sintering densification, optimizes the ability of solid solution to form a supersaturated solid solution, and increases the substitution sites of heavy rare earth.
[0022] (4) Based on the characteristic that heavy rare earth elements can improve the stability of the 2:17H phase, the present invention further optimizes the microstructure and magnetic properties by designing sintering and solid solution processes associated with heavy rare earth components on the basis of adding isothermal annealing. Description of the drawings:
[0023] The present invention will now be described by way of example with reference to the accompanying drawings, in which:
[0024] Figure 1 In order to increase the process diagram of ingot annealing, in the conventional Sm 2 Co 17 In the preparation process of sintered magnet, an isothermal annealing process of the ingot is added.
[0025] Figure 2 The XRD pattern of the ingot after annealing is shown in Figure 2. 1-x RE x (Co bal Fe a Cu b Zr c ) z The alloy ingot is isothermally annealed. Wherein ac corresponds to Examples 1-3 respectively. Figure 1-3 As shown in the figure, after isothermal annealing of the ingot, the intensity of the characteristic peak (2 0 3) of 2:17H decreases, which means that the content of the 2:17H phase is reduced, which is beneficial to suppress the subsequent element segregation problem. In addition, after isothermal annealing of the ingot, the peak width is narrow, which indicates that the crystallinity is improved, the crystal stress and defects generated during casting are eliminated, and it is beneficial to increase the substitution sites of heavy rare earth.
[0026] Figure 3 Figure 1 is the in-situ distribution of the elements of the ingot before and after annealing, where Figures a and b correspond to Example 1-2 and Example 1-2 respectively. The magnet composition corresponding to a is Sm(Co bal Fe 0.15 Cu 0.1 Zr 0.025 ) 7.6 , where b is the same composition of the ingot annealing magnet. The corresponding magnet composition of c is Sm 0.4 Er 0.6 (Co bal Fe 0.15 Cu 0.1 Zr 0.025 ) 7.6 , d is the same composition of the ingot annealing magnet. As shown in ab, in the heavy rare earth-free magnet, the equiaxed crystals in the alloy disappear after isothermal annealing, and the ingot is a single 1-7H phase, which is conducive to obtaining a short-range ordered precursor in the subsequent solid solution magnet. As shown in cd, although there is a 2:17H phase in the ingot, there is obvious element segregation before the ingot annealing, which is rich in Co, Fe, Cu, Zr and Sm; after annealing, the element uniformity is greatly improved. Except for a slight Fe element gap, the overall organization is uniform, which enhances the element diffusion in the solid solution process of the magnet. Specific implementation method:
[0027] The present invention will be further described below in conjunction with examples and comparative examples, but the present invention is not limited to the following examples.
[0028] Comparative Example 1:
[0029] Conventional magnets are prepared by conventional powder metallurgy, with a design composition of Sm(Co bal Fe0.15 Cu 0.1 Zr 0.025 ) 7.6 , the corresponding metal alloy is baked in a vacuum medium frequency melting furnace and filled with argon, and the temperature is gradually raised to complete melting, and the temperature is kept for 5 minutes until it is completely uniform and then poured into a copper mold; the ingot is coarsely crushed under the protection of argon, and then crushed into a powder with an average particle size of about 4.1μm by a jet mill process. Before sintering, the powder is placed in a 2.0T magnetic field for arrangement and pressing, and then pressed by cold isostatic pressing. The green body is sintered at 1210℃ for 1h, followed by a 5h solid solution treatment at 1180℃, and finally air-cooled to room temperature. The solid solution sample is then isothermally aged at 830℃ for 16h, then slowly cooled to 400℃ at a rate of 0.7℃ / min, and isothermally aged at 400℃ for 6 hours. A common 2:17 type SmCo-based magnet without heavy rare earth is obtained, defined as A1, and the magnetic properties are tested in a PFM tester. The results are as follows:
[0030] Magnet A1: B r =9.82kG, H cj =42.26kOe, (BH) max =22.61MGOe, H k =18.48kOe, H k / H cj =43.72%, α 20-150℃ =-0.054% / ℃.
[0031] Embodiment 1:
[0032] Conventional magnets are prepared by conventional powder metallurgy, and an ingot annealing process is added. Specifically, the designed composition is Sm(Co bal Fe 0.15 Cu 0.1 Zr 0.025 ) 7.6, the corresponding metal alloy is baked in a vacuum medium frequency melting furnace and filled with argon, and the temperature is gradually raised to complete melting, and the temperature is kept for 5 minutes until it is completely uniform and then poured into a copper mold; the resulting ingot is isothermally annealed at 1200℃ for 15 hours under the protection of argon, and quickly air-cooled to room temperature to obtain a uniform supersaturated solid solution of elements; the annealed ingot is then coarsely crushed under the protection of argon, and then crushed into a powder with an average particle size of about 4.2μm by a jet mill process. Before sintering, the powder is placed in a 2.0T magnetic field for arrangement and pressing, and then pressed by cold isostatic pressing. The green body is sintered at 1210℃ for 1h, followed by a solution treatment at 1170℃ for 5h, and finally air-cooled to room temperature. The solid solution sample is then isothermally aged at 830℃ for 16h, then slowly cooled to 400℃ at a rate of 0.7℃ / min, and isothermally aged at 400℃ for 6h. A common 2:17 type SmCo-based magnet without heavy rare earth was obtained, defined as A2, and put into a PFM tester to test the magnetic properties. The results are as follows:
[0033] Magnet A2: B r =10.02kG, H cj =39.86kOe, (BH) max =24.18MGOe, H k =22.56kOe, H k / H cj =56.71%, α 20-150℃ =-0.035% / ℃. After isothermal annealing, the H of ordinary magnets k The squareness is improved, the remanence and magnetic energy product are increased, and the remanence temperature coefficient of the magnet is improved.
[0034] Comparative Example 2:
[0035] Conventional magnets are prepared using conventional powder metallurgy, with a design composition of Sm 0.4 Er 0.6 (Co bal Fe 0.15 Cu 0.1 Zr 0.025 ) 7.6, the corresponding metal alloy was baked in a vacuum medium frequency melting furnace and filled with argon, and the temperature was gradually raised to complete melting, and the temperature was kept for 5 minutes until it was completely uniform and then poured into a copper mold; the ingot was coarsely crushed under the protection of argon, and then crushed into a powder with an average particle size of about 4.2μm by a jet mill process. Before sintering, the powder was placed in a 2.0T magnetic field for arrangement and pressing, and then pressed by cold isostatic pressing. The green body was sintered at 1212℃ for 2.5h, followed by a 10h solid solution treatment at 1190℃, and finally air-cooled to room temperature. The solid solution sample was then isothermally aged at 830℃ for 16h, then slowly cooled to 400℃ at a rate of 0.7℃ / min, and isothermally aged at 400℃ for 6h. A high-stability 2:17 type SmCo-based magnet was obtained, defined as B1, and the magnetic properties were tested in a PFM tester. The results are as follows:
[0036] Magnet B1: B r =8.92kG, H cj =29.83kOe, (BH) max =18.5MGOe, H k =7.74kOe, H k / H cj =36.86%, α 20-150℃ =+0.004% / ℃.
[0037] Embodiment 2:
[0038] Conventional magnets are prepared by conventional powder metallurgy, and the ingot annealing process is added. Specifically, the design composition is Sm 0.4 Er 0.6 (Co bal Fe 0.15 Cu 0.1 Zr 0.025 ) 7.6, the corresponding metal alloy is baked in a vacuum medium frequency melting furnace and filled with argon, and the temperature is gradually raised to complete melting, and the temperature is kept for 5 minutes until it is completely uniform and then poured into a copper mold; the resulting ingot is isothermally annealed at 1200℃ for 20 hours under the protection of argon, and quickly air-cooled to room temperature to obtain a uniform supersaturated solid solution of elements; the annealed ingot is then coarsely crushed under the protection of argon, and then crushed into a powder with an average particle size of about 4.2μm by a jet mill process. Before sintering, the powder is placed in a 2.0T magnetic field for arrangement and pressing, and then pressed by cold isostatic pressing. The green body is sintered at 1212℃ for 2.5h, followed by a 10h solid solution treatment at 1190℃, and finally air-cooled to room temperature. The solid solution sample is then isothermally aged at 830℃ for 16h, then slowly cooled to 400℃ at a rate of 0.7℃ / min, and isothermally aged at 400℃ for 6h. A high stability 2:17 type SmCo based magnet was obtained, defined as B2, and put into a PFM tester to test the magnetic properties. The results are as follows:
[0039] Magnet B2: B r =8.81kG, H cj =30.01kOe, (BH) max =18.08MGOe, H k =8.82kOe, H k / H cj =56.24%, α 20-150℃ =0% / ℃. After isothermal annealing, the H of high stability magnets k The squareness is improved significantly, the remanence and magnetic energy product are slightly reduced, and a zero remanence temperature coefficient magnet is obtained in the temperature range of 20-150℃.
[0040] Comparative Example 3:
[0041] Conventional magnets are prepared using conventional powder metallurgy, with a design composition of Sm 0.4 Tm 0.6 (Co bal Fe 0.15 Cu 0.1 Zr 0.025 ) 7.6, the corresponding metal alloy is baked in a vacuum medium frequency melting furnace and filled with argon, and the temperature is gradually raised to complete melting, and the temperature is kept for 6 minutes until it is completely uniform and then poured into a copper mold; the ingot is coarsely crushed under the protection of argon, and then crushed into a powder with an average particle size of about 3.9μm by a jet mill process. Before sintering, the powder is placed in a 2.0T magnetic field for arrangement and pressing, and then pressed by cold isostatic pressing. The green body is sintered at 1212℃ for 2.5h, followed by a 10h solid solution treatment at 1190℃, and finally air-cooled to room temperature. The solid solution sample is then isothermally aged at 830℃ for 16h, then slowly cooled to 400℃ at a rate of 0.7℃ / min, and isothermally aged at 400℃ for 6h. A high-stability 2:17 type SmCo-based magnet is obtained, defined as C1, and the magnetic properties are tested in a PFM tester. The results are as follows:
[0042] Magnet C1: B r =9.25kG, H cj =9.94kOe, (BH) max =18.74MGOe, H k =5.82kOe, H k / H cj =58.55%, α 20-150℃ =-0.008% / ℃.
[0043] Embodiment 3:
[0044] Conventional magnets are prepared by conventional powder metallurgy, and the ingot annealing process is added. Specifically, the design composition is Sm 0.4 Tm 0.6 (Co bal Fe 0.15 Cu 0.1 Zr 0.025 ) 7.6, the corresponding metal alloy was baked in a vacuum medium frequency melting furnace and filled with argon, and the temperature was gradually raised to complete melting, and the temperature was kept for 5 minutes until it was completely uniform and then poured into a copper mold; the resulting ingot was isothermally annealed at 1210℃ for 20 hours under the protection of argon, and quickly air-cooled to room temperature to obtain a uniform supersaturated solid solution of elements; the annealed ingot was then coarsely crushed under the protection of argon, and then crushed into a powder with an average particle size of about 3.9μm by a jet mill process. Before sintering, the powder was placed in a 2.0T magnetic field for arrangement and pressing, and then pressed by cold isostatic pressing. The green body was sintered at 1212℃ for 2.5h, followed by a 10h solid solution treatment at 1190℃, and finally air-cooled to room temperature. The solid solution sample was then isothermally aged at 830℃ for 16h, then slowly cooled to 400℃ at a rate of 0.7℃ / min, and isothermally aged at 400℃ for 6h. A high stability 2:17 type SmCo based magnet was obtained, defined as B2, and put into a PFM tester to test the magnetic properties. The results are as follows:
[0045] Magnet C2: B r =9.00kG, H cj =10.35kOe, (BH) max =18.13MGOe, H k =6.0kOe, H k / H cj =57.97%, α20-150℃=0% / ℃. After isothermal annealing, the H k The remanence and magnetic energy product are slightly reduced, and a zero remanence temperature coefficient magnet is obtained in the temperature range of 20-150℃.
[0046] Table 1 Magnet properties of ingot before and after isothermal annealing (the first 5 corresponding temperatures are room temperature 25°C)
[0047]
[0048] In summary, the above technical solution provided by the present invention can significantly improve the H k , squareness, and enhanced high temperature performance of high stability magnets.
[0049] In addition, in addition to Examples 1-3 in the present invention, the inventors conducted a large number of experiments using the technical solutions and original conditions described in the present invention, and also obtained a high-stability 2:17 SmCo-based magnet with improved squareness.
[0050] It should be understood that the above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
[0051] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for simultaneously optimizing the squareness and remanence temperature coefficient of 2:17 type samarium cobalt sintered magnets, characterized in that: The preparation process includes: melting ingot - isothermal annealing - powder making - orientation pressing - sintering - solution treatment - aging. An isothermal annealing process is added after melting the ingot to inhibit the generation of 2:17H in the ingot and improve element segregation, improve the composition uniformity of the alloy, obtain a more uniform supersaturated solid solution after solution treatment, improve the cellular structure in the magnet after aging, and improve the performance of the magnet.
2. The method for simultaneously optimizing the squareness and remanence temperature coefficient of 2:17 type samarium cobalt sintered magnet according to claim 1, characterized in that: The nominal composition of the magnet is Sm 1-x RE x (Co bal Fe a Cu b Zr c ) z , where RE = one or more of heavy rare earth elements such as Dy, Er, Gd and Tm; a, b, c, x satisfy the following relationship: 0≤x≤0.6, 0.1≤a≤0.2, 0.06≤b≤0.12, 0.02≤c≤0.03, 6.9≤z≤7.9, bal refers to 1-abc.
3. The method for simultaneously optimizing the squareness and remanence temperature coefficient of 2:17 type samarium cobalt sintered magnet according to claim 1, characterized in that: The specific steps include: (1) Based on the nominal composition of Sm 1-x RE x (Co bal Fe a Cu b Zr c ) z Select rare earth, metal cobalt, metal iron, metal copper, metal zirconium, put them into a crucible, fill them with argon gas for smelting after the materials are baked under vacuum, and then pour them into a water-cooled copper mold to obtain an ingot with a thickness of 1.8-2.0 cm; (2) The ingot obtained in step (1) is heated to 1190-1210° C. in a tube furnace, filled with argon gas, and isothermally annealed for 5-20 hours, followed by air cooling. (3) the ingot in step (2) is coarsely crushed in a medium crusher, 1.5-3 wt.% of an antioxidant is added to prevent oxidation, and then the ingot is ground into a powder with an average particle size of about 3.5-4.5 μm by a jet mill process; (4) Adding 1.5-3.0 wt.% of an antioxidant to the powder obtained in step (3) in a glove box to prevent oxidation and increase lubrication, and then mixing in a three-dimensional mixer for 2-5 hours; (5) placing the powder obtained in step (4) in a magnetic field of 1.7-2.0 T for arrangement and pressing, and then pressing and molding by cold isostatic pressing at a pressure of 200-280 MPa and a holding time of 120-180 s; (6) placing the green body obtained in step (5) into a vacuum sintering furnace for sintering and solution treatment, sintering the green body at 1210-1230° C. for 1-5 hours, then performing solution treatment at 1150-1200° C. for 5-30 hours, and finally air cooling to room temperature, thereby obtaining a supersaturated solid solution; (7) The solid solution magnet obtained in step (6) is placed in a tubular furnace, and then the solid solution sample is isothermally aged at 810-850°C for 10-20 hours under the protection of argon, and then slowly cooled to 400°C at a rate of 0.5-0.8°C / min, and isothermally aged at 400°C for 3-6 hours to obtain a SmRE(CoFeCuZr)z magnet.
4. The method for simultaneously optimizing the squareness and remanence temperature coefficient of 2:17 type samarium cobalt sintered magnet according to claim 1, characterized in that: The sintering process and the solid solution process are selected according to the heavy rare earth content. The larger the heavy rare earth element content (x), the longer the sintering time and the higher the solid solution temperature in step (6).
5. An optimized 2:17 type samarium cobalt sintered magnet prepared according to the method described in any one of claims 1 to 4.
Citation Information
Patent Citations
Rare earth permanent magnet produced by applying abundant rare earth cerium (Ce) and preparation method thereof
CN103123839A
Sm2Co17 type sintered magnet with low temperature coefficient and preparation method thereof
CN111091943A
Preparation method of super high coercivity and low-Co type Sm-Co nanocrystalline alloy
CN102140598A
Preparation method of samarium-cobalt-nitrogen permanent magnet material
CN105788795A
High-temperature high-coercivity samarium-cobalt permanent magnet material and preparation method thereof
CN108039258A
Cited By
Samarium cobalt permanent magnet and preparation method thereof
CN120473326A
Samarium cobalt permanent magnet with high remanence and low remanence temperature coefficient and preparation method thereof
CN121790111A